Comparison of macular thickness, retinal nerve fiber layer thickness and optic nerve head parameters in HbE/Beta thalassemia and control - Dezhao, Sai (2016)
Introduction HbE/ β-thalassemia is one of the hemoglobinopathy that commonly found in South East Asia (SEA) and it has become a severe public health problem today. Apart from the pathological anemia, they also share other common features like hepatosplenomegaly and craniofacial bony deformities. Ocular biometry can be affected as well due to abnormal growth of the orbital bone. Other than these, structure of the retina and the optic nerve may be altered in these patients. Objective To compare mean macular thickness, retinal nerve fiber layer (RNFL) thickness and optic nerve head (ONH) parameters between HbE/ β-thalassemia group and control. Methods This is a cross-sectional study conducted in Hospital Universiti Sains Malaysia from June 2014 till March 2016. Patients with confirmed HbE/ β-thalassemia and healthy population were selected based on the inclusion and exclusion criteria. Baseline macular thickness, RNFL thickness and ONH parameters were measured by using Cirrus HD-OCT. Statistical analysis was performed using SPSS version 22.0. Results A total of 132 participants were recruited (66 participants in HbE/ β-thalassemia group and 66 participants in control). There was no significant difference in mean macular thickness in between the two groups. No significant different found in the mean RNFL thickness in between HbE/ β- thalassemia and control. There was also no significant difference in ONH parameters between two groups. Conclusion The study revealed that there was no significant differences in both mean macular thickness, RNFL thickness and ONH parameters in between HbE/ β-thalassemia and normal population.